Case Report: Solar retinopathy following exposure to reflected sunlight (Ukrainian Journal of Ophthalmology, 2025)
Background: Radiation damage to the eye is most commonly caused by sunlight. Solar retinopathy is a form of retinal damage that occurs after exposure to solar radiation, with the most common symptoms being reduced vision and central scotoma.Purpose: To report a case of retinal damage following exposure to reflected sunlight with a favorable outcome.Materials and Methods: The patient underwent visual acuity, tonometry, ophthalmoscopy, optical coherence tomography (OCT), fundus photography and fluorescein angiography.Results: At six months after initiation of treatment, the patient reported that the white spot before his left eye decreased in size, and became transparent and practically unnoticeable to him. In solar retinopathy, the OCT appearance of retinal defect may vary, depending on the severity of damage, but provides evidence of destruction of the outer retinal layers.Conclusion: We reported a case of retinal damage following exposure to reflected sunlight with a favorable outcome. Follow-up OCT showed complete restoration of the affected retinal structures in one eye and the residual changes in the outer photoreceptor layer and RPE in the fellow eye. Therefore, solar retinopathy can occur with OCT evidence of retinal destruction following retinal damage from direct and/or reflected sunlight.
Keywords: retina; photoreceptors; pigment epithelium; solar retinopathy; reflected sunlight